2020
DOI: 10.1111/cdev.13393
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Prerequisites for Generative Learning: Why Some Learning Strategies Are More Effective Than Others

Abstract: This study examined age-related differences in the effectiveness of two generative learning strategies (GLSs). Twenty-five children aged 9-11 and 25 university students aged 17-29 performed a facts learning task in which they had to generate either a prediction or an example before seeing the correct result. We found a significant Age 9 Learning Strategy interaction, with children remembering more facts after generating predictions rather than examples, whereas both strategies were similarly effective in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 60 publications
(85 reference statements)
2
17
0
2
Order By: Relevance
“…Knowledge of prerequisites thus suggests that although generating examples can work well for undergraduates, it should be rather ineffective for elementary-school children. In keeping with this hypothesis, results showed that elementary-school children learned less when they generated examples than when they generated predictions, whereas undergraduates learned comparably well in both conditions (Breitwieser & Brod, 2021). The difference in effectiveness between generating predictions and examples was related to children's reasoning abilities, in line with its assumed role as a prerequisite.…”
Section: How Considering Prerequisites For Active Learning Could Guidsupporting
confidence: 52%
See 3 more Smart Citations
“…Knowledge of prerequisites thus suggests that although generating examples can work well for undergraduates, it should be rather ineffective for elementary-school children. In keeping with this hypothesis, results showed that elementary-school children learned less when they generated examples than when they generated predictions, whereas undergraduates learned comparably well in both conditions (Breitwieser & Brod, 2021). The difference in effectiveness between generating predictions and examples was related to children's reasoning abilities, in line with its assumed role as a prerequisite.…”
Section: How Considering Prerequisites For Active Learning Could Guidsupporting
confidence: 52%
“…Third, knowledge of prerequisites for active learning can help instructors choose those active-learning practices that are likely to work best for a particular group of students and to provide the right level of guidance. In a recent study that illustrates this approach (Breitwieser & Brod, 2021), late-elementary-school children and undergraduates studied science facts using either of two active-learning practices: They had to either generate a prediction or come up with an example before seeing the correct information (a numerical fact). These two active-learning practices were contrasted because their cognitive prerequisites are known to differ.…”
Section: How Considering Prerequisites For Active Learning Could Guidmentioning
confidence: 99%
See 2 more Smart Citations
“…A less ambitious approach would be to cross-sectionally compare two different GLSs or two different implementations of one GLS between age groups and to examine whether agerelated differences in effectiveness are related to differences in prerequisites. A recent study that took just this approach compared the effectiveness of two GLSs in late-elementary-school children and university students (Breitwieser and Brod 2020). Participants were given a learning task in which they generated either predictions or examples before being presented with the correct information (i.e., numerical facts).…”
Section: Discussionmentioning
confidence: 99%